2017
DOI: 10.1002/mrd.22881
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the complexity of vitellogenins and their receptors in the tetraploid Atlantic salmon (Salmo salar): Ancient origin of the phosvitin‐less VtgC in chondrichthyean fishes

Abstract: Egg yolk proteins are mainly derived from vitellogenin (Vtg), and serve as essential nutrients during early development in oviparous organisms. Vertebrate Vtgs are predominantly synthesized in the liver of maturing females, and are internalized by the oocyte after binding to specific surface receptors (VtgR). Here, we clarify the evolutionary history of vertebrate Vtgs, including the teleost VtgC, which lacks phosvitin, and investigate the repertoire of Vtgs and VtgRs in the tetraploid Atlantic salmon (Salmo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 88 publications
(117 reference statements)
2
6
0
Order By: Relevance
“…Recently, high expression of vitellogenin receptors in ovaries from females during the same period have been observed, supporting our observation (Andersen et al. ) The early development of vitellogenic oocytes found here appears to be more similar to observations in rainbow trout ( Oncorhynchus mykiss ; Sumpter et al. ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Recently, high expression of vitellogenin receptors in ovaries from females during the same period have been observed, supporting our observation (Andersen et al. ) The early development of vitellogenic oocytes found here appears to be more similar to observations in rainbow trout ( Oncorhynchus mykiss ; Sumpter et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…This is somewhat earlier than expected compared to other studies in Atlantic salmon females, where secondary growth phase oocytes were observed equally early under similar photoperiod treatment, but not any vitellogenic oocytes (Taranger et al 1998(Taranger et al , 1999Andersson et al 2009). Recently, high expression of vitellogenin receptors in ovaries from females during the same period have been observed, supporting our observation (Andersen et al 2017) The early development of vitellogenic oocytes found here appears to be more similar to observations in rainbow trout (Oncorhynchus mykiss; Sumpter et al 1984).…”
Section: Discussionsupporting
confidence: 92%
“…Jawed vertebrates produce three major forms of Vtg arising from a vtg gene cluster that was present in the ancestor of tetrapods and ray-finned fish (Babin, 2008; Finn et al, 2009). During vertebrate evolution these ancestral vtg genes were subject to whole genome duplications, loss of paralogs and lineage-specific tandem duplications, giving rise to substantial variation in the repertoire and number of vtg genes present in an individual species, especially among teleost fish (Andersen et al, 2017). The linear yolk protein domain structure of complete teleost Vtgs is: NH 2 -lipovitellin heavy chain (LvH)-phosvitin (Pv)-lipovitellin light chain (LvL)-beta component (β’c)-C-terminal component (Ct)-COOH (Patiño and Sullivan, 2002; Hiramatsu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Jawed vertebrates produce three major forms of Vtg arising from a vtg gene cluster that was present in the ancestor of tetrapods and ray-finned fish (Babin, 2008;Finn, Kolarevic, Kongshaug, & Nilsen, 2009). During vertebrate evolution these ancestral vtg genes were subject to whole genome duplications, loss of paralogs and lineage-specific tandem duplications, giving rise to substantial variation in the repertoire and number of vtg genes present in an individual species, especially among teleost fish (Andersen et al, 2017). The linear yolk protein domain structure of complete teleost Vtgs is NH 2 -lipovitellin heavy chain (LvH)phosvitin (Pv)-lipovitellin light chain (LvL)-β component (β'c)-C-terminal component (Ct)-COOH (Hiramatsu, Cheek, Sullivan, Matsubara, & Hara, 2005;Patiño & Sullivan, 2002).…”
mentioning
confidence: 99%